Creating a Classroom Community in the Age of Covid-19 - Madden, Amanda (The sixteenth century journal, 2020)
In this article, the author offers a personal narrative of their experiences teaching a remote college-level course during the COVID-19 pandemic, examining the works of Renaissance authors who emphasize that pleasant and enlightening conversation is a way to maintain mental and emotional health and how that can serve as inspiration for contemporary circumstances.